Long-term forest soil warming alters microbial communities in temperate forest soils - DeAngelis, Kristen M.; Pold, Grace; Topçuoğlu, Begüm D.; van Diepen, Linda T. A.; Varney, Rebecca M.; Blanchard, Jeffrey L.; Melillo, Jerry; Frey, Serita D. (Frontiers in Microbiology, 2015)
Soil microbes are major drivers of soil carbon cycling, yet we lack an understanding of how climate warming will affect microbial communities. Three ongoing field studies at the Harvard Forest Long-term Ecological Research (LTER) site (Petersham, MA) have warmed soils 5oC above ambient temperatures for 5, 8 and 20 years. We used this chronosequence to examine soil microbial communities in response to chronic warming. Bacterial community composition was studied using Illumina sequencing of the 16S ribosomal RNA gene, and bacterial and fungal abundance were assessed using quantitative PCR. Only the 20-year warmed site exhibited significant change in bacterial community structure in the organic soil horizon, with no significant changes in the mineral soil. The dominant taxa, abundant at 0.1% or greater, represented 0.3% of the richness but nearly 50% of the observations (sequences). Individual members of the Actinobacteria, Alphaproteobacteria and Acidobacteria showed strong warming responses, with one Actinomycete decreasing from 10% to 2% relative abundance with warming. We also observed a significant decrease in mean bacterial ribosomal RNA gene copy number in warming plots compared to controls, a trait linked to maximum growth rate or trophic strategy among bacteria. Increased bacterial alpha diversity, shifting beta diversity, decreased fungal abundance and increased abundance of bacteria with low rRNA operon copy number, including Alphaproteobacteria and Acidobacteria suggest that more or alternative niche space is being created over the course of long-term warming.